An app-enhanced cognitive fitness training program for athletes: The rationale and validation protocol - Aidman, Eugene; Fogarty, Gerard J.; Crampton, John; Bond, Jeffrey; Taylor, Paul; Heathcote, Andrew; Zaichkowsky, Leonard (Frontiers in Psychology, 2022)
The core dimensions of cognitive fitness, such as attention and cognitive control, are emerging through a transdisciplinary expert consensus on what has been termed the Cognitive Fitness Framework (CF2). These dimensions represent key drivers of cognitive performance under pressure across many occupations, from first responders to sport, performing arts and the military. The constructs forming the building blocks of CF2 come from the RDoC framework, an initiative of the US National Institute of Mental Health (NIMH) aimed at identifying the cognitive processes underlying normal and abnormal behaviour. Similar to physical conditioning, cognitive fitness can be improved with deliberate practice. This paper reports the development of a prototype cognitive fitness training program for competitive athletes and the protocol for its evaluation. The program is focused on primary cognitive capacities and subtending skills for adjusting training rhythms and enhancing readiness for competition. The project is driven by the Australian Psychological Society’s College of Sport & Exercise Psychology and includes the development of a Cognitive Gym program for a smartphone app-enhanced implementation. Its key building blocks are training protocols (drills) connected by a periodised training plan. A website with background supporting resources has also been developed as part of the project. National-level training squads will participate in a three-week pilot evaluation protocol, assessing the program’s efficacy and usability through gamified cognitive assessment of participants’ training gains and coaching staff evaluations, respectively. Both near and far transfer of training effects will be examined.